The Role of Recipient's Absorptive Capacity in Knowledge Transfer - Heikkilä, Maria (My University, 2009)
This research studied the role of recipient’s absorptive capacity in knowledge transfer between UK and Finland. The objective of this study is to identify factors that affect the level of recipient’s absorptive capacity. In theoretical parts of the study focus on five major factors that determine recipient’s absorptive capacity: Learning ability, Motivation, Retentive capacity, Organizational culture and Contexts on knowledge transfer. The findings reveal that motivation of the employee, and its related factors such as sound rewarding systems, proper training and expertise in different fields, trust and teamwork between employees proved to be the most influential factors for the level of recipient’s absorptive capacity. The findings don’t support that learning ability affects the recipient greatly as the existing literatures suggested. Recipients don’t lack the ability to learn, but the opportunity and time to learn. Besides, their retentive ability, as ability to institutionalise and repeat tacit knowledge seems very challenging in the case company. Organizational culture and contexts’ related factors on knowledge transfer proved to be less helpful in explaining on recipient’s absorptive capacity compared with other factors. This study was carried out by an in-depth single case study, and the methodology adopted in this research is qualitative method. The case company chosen is Tao Finland Oy, where the researcher has been working since company was established. Data collection was based on six semi-structured open-ended interviews and direct observation of the researcher.
Keywords: Recipient’s Absorptive Capacity; Motivation; Retentive ability; Knowledge Transfer; fi=Management|; fi=Master's Degree Programme in International Business|